Synthesis of C‐14 labeled Rac‐(3R, 2S)‐glycopyrronium bromide. (1st July 2020) - Bergare, Jonas; Nixon, Neil; Newsome, Jeffery; Thunberg, Linda; Elmore, Charles S.
Abstract : In an effort to better understand the drug metabolism and pharmacokinetics (DMPK) properties of glycopyrronium bromide (1 ), a muscarinic acetylcholine receptor antagonist, a C‐14 labeled isotopologue was required. The compound was prepared in five synthetic steps and 5% overall radiochemical yield from Cu 14 CN. During the synthesis, an unexpected decarboxylation of phenylglyoxylate resulted in the loss of much of the radiolabeled compound. Chiral chromatography was utilized to isolate and deliver the proper pair of enantiomers as [ 14 C]‐1 . Abstract : Glycopyrronium bromide (1 ) is a muscarinic acetylcholine receptor antagonist and was prepared in C‐14 labeled labeled form in five synthetic steps and 5% overall radiochemical yield from Cu 14 CN. Chromatography using a chiral stationary phase was used isolate and deliver the proper pair of enantiomers. During the synthesis, an unexpected decarboxylation of [ 14 C] phenylglyoxylate resulted in the loss of much of the radiolabeled compound.